Electric Energy Management Model based on Indicators for power companies with cogeneration systems in Nicaragua - Blanco-Orozco, Napoleón Vicente (2018)
In this article a model of integral management of electric energy based on indicators, MGEI, is proposed. The model proposal is based on the grounded theory, with the support of computer tools such as Atlas ti 7 and SPSS 23, and consultation with experts and a focal group. The MGEI is structured in stages: The first stage is the company Chief Executive Officer (CEO) CEO decision; the second stage is the energy review, that includes energy management indicators; the third stage is the implementation of energy saving measures, and the fourth stage is the evaluation of the energy saving measures, the monitoring of indicators during the application of energy saving measures, and the comparison between the energy baseline and the indicators mentioned.